38‐4: A 2T1C AMOLED Display with External Compensation Reducing On‐Panel Current Variations to 0.079%. Issue 1 (25th September 2020) - Verschueren, Lynn; Ameys, Marc; Velazquez Lopez, Mauricio; Smout, Steve; Ke, Tung Huei; Vandenplas, Erwin; Kronemeijer, Auke Jisk; Heremans, Paul; Genoe, Jan; Dehaene, Wim; Myny, Kris
Abstract : This paper presents a new compensation principle using a 2T1C pixel circuit. The implementation shows significant improvement in uniformity for all grey‐levels, due to compensation for both VT and β‐factor variations. The resulting current variation after compensation in the characterized display area reaches values down to 0.079%.